Analysis Of Learning Knowledge In Physical Education, Sports, And Health Among Students In Grades 4, 5, And 6 At Sdn 17 Pangkal Duri Ilir In 2025 - Rahmat Firdaus; Adhe Saputra; Ahmad Muzaffar (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Physical education aims to develop psychomotor, cognitive, and affective aspects. Knowledge is the result of knowing after a person perceives a particular object. This study is a descriptive study with one variable without making comparisons or linking it to other variables. The research sample used total sampling technique, which means that all students in grades 4, 5, and 6 at SDN 17 Pangkal Duri Ilir were used as the research sample. The instrument used in this study was a questionnaire. The results of this study show that the majority of respondents had very high knowledge, with 20 students (25%). The remaining 5 students (6.25%) have a high level of knowledge, 10 students (12.25%) have an average level of knowledge, 10 students (12.25%) have a low level of knowledge, and 35 students (43.75%) have a very low level of knowledge.